2000
DOI: 10.1074/jbc.275.11.8133
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor Stimulates Surface Expression and Activity of Na+/H+ Exchanger NHE3 via Mechanism Involving Phosphatidylinositol 3-Kinase

Abstract: Na؉ /H ؉ exchanger NHE3 is a plasma membrane (PM) protein, which contributes to Na ؉ absorption in the intestine. Growth factors stimulate NHE3 via phosphatidylinositol 3-kinase (PI3-K), but mechanism of this process is not clear. To examine the hypothesis that growth factors stimulate NHE3 by modulating NHE3 recycling, and that PI3-K participates in this mechanism, we used PS120 fibroblasts expressing a fusion protein of NHE3 and green fluorescent protein. At steady state, ϳ25% of cellular NHE3 content was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 45 publications
4
80
1
Order By: Relevance
“…Another possibility is that PI3K may regulate trafficking of transport proteins to and from the plasma membrane. In support of this hypothesis it has been previously shown that PI3K is intimately involved in cytoskeletal reorganization and membrane trafficking in a number of systems, including intestinal epithelial cells (51)(52)(53)(54)(55). Furthermore, a growing body of evidence suggests that epithelial secretory responses to cAMP-dependent agonists are not only dependent on phosphorylation and activation of CFTR channels resident in the apical membrane but are also dependent on rapid trafficking of the channel between endosomes and the plasma membrane (56 -59).…”
Section: Discussionmentioning
confidence: 77%
“…Another possibility is that PI3K may regulate trafficking of transport proteins to and from the plasma membrane. In support of this hypothesis it has been previously shown that PI3K is intimately involved in cytoskeletal reorganization and membrane trafficking in a number of systems, including intestinal epithelial cells (51)(52)(53)(54)(55). Furthermore, a growing body of evidence suggests that epithelial secretory responses to cAMP-dependent agonists are not only dependent on phosphorylation and activation of CFTR channels resident in the apical membrane but are also dependent on rapid trafficking of the channel between endosomes and the plasma membrane (56 -59).…”
Section: Discussionmentioning
confidence: 77%
“…The best-characterized mechanism of NHE3 up-regulation is recruitment to the plasma membrane (22,23). The data show that this is also the mechanism by which Na ϩ -glucose cotransport activates NHE3.…”
Section: Discussionmentioning
confidence: 80%
“…We considered NHE3 phosphorylation as a potential regulatory mechanism (21), but, although documented, the role of phosphorylation in NHE3 regulation remains to be established. We also considered trafficking of NHE3 between intracellular vesicles and the apical membrane, which has been described as a mechanism of acute NHE3 up-regulation (22,23). To explore this possibility, we measured surface NHE3 before and after initiation of Na ϩ -glucose cotransport.…”
Section: Translocation Of Nhe3 To the Apical Membrane Is Associated Wmentioning
confidence: 99%
“…Basal NHE3 activity was inhibited by exposure to the PI3K inhibitors, viz. LY594002 (31) and wortmannin (32,33) at low doses, and acutely stimulated NHE3 was reduced by the same inhibitors between 50 and 100% based on the cell type expressing NHE3 and the ligand studied (FGF in PS120 cells by 50% (32); lysophosphatidic acid in opossum kidney cells by 100%) (31). These previous studies of PI3K dependence of basal and acutely stimulated NHE3 activity plus the rapid stimulation of NHE3 activity when PI(3,4,5) 3 was added to the Table 1.…”
Section: Discussionmentioning
confidence: 99%